Z działalności ambasadora Waltera Bedell Smitha w okresie pierwszego kryzysu berlińskiego (1948-1949) - Wasiewicz, Magdalena (Acta Universitatis Lodziensis. Folia Historica, 2005)
The article presents the activity US Ambassador to Soviet Union W. B. Smith during the First Berlin Crisis, which was one of the reasons why the Cold War began. On June 24, 1948 Soviet forces implemented a blockade of Berlin halting all railroad tralTic, the major means of transporting food and fuel into the city. The blockade was a response to the Western currency reform announced on June 22, the decisions taken at the London conference earlier in the month that established the foundation for West Germany, and the Soviet desire to drive the three Western powers out of Berlin. At the end of June the United States announced that an expanded airlift would begin to carry food and supplies into Berlin. The negotiations held by Allies in Berlin did not lead to the solution to the dangerous situation. They were moved to Moscow, when the ambassadors of the US, France and the representative of United Kingdom were to talk to USRR leaders. The representatives of the West were to make Stalin abolish the blockade getting a give-and-take in return. During the first meeting the ambassadors with Joseph Stalin and Foreign Minister Molotov (August 3), Smith told that the three Western powers were in Berlin by right, and they intended to remain there. He said the Western Big Three were eager to resolve differences with the Soviet Union, but no negotiations could take place while the blockade remained in effect. The next meeting with Molotov Ambassador Smith consistently emphasized two points. Firstly that the Western powers were in Berlin by right and not at the sufferance of the Soviet Union, and secondly that the decision taken at the London conference would not be suspended or delayed. Ambassador Smith, along with the British and French ambassadors, met Joseph Stalin again to discuss Berlin issues (August 23). A tentative agreement between the two sides was reached regarding the currency issue, but the arrangements for its implementation were to be worked out by the military governors in Berlin. In September the four military governors in Berlin announced they could not rcach an agreement based on the Moscow directive. In the end or September France, the United Kingdom, and the United States sent identical letters to the secretary general of the United Nations informing him that the Berlin situation constituted a threat to world peace as defined in Chapter VII of the United Nations Charter. Ihe Western powers requested that the Berlin issue be taken up by the Security Council as quickly as possible. The negotiation in Moscow in which Walter Bedell Smith participated ended unsuccessfully and the blockade of Berlin was not suspended by Russians until 1949.